Open-source modeling and structural deformation analysis of a solar-powered charging station using freeCAD - Kasturi, Kasturi; P, Regan Rahadian; Akhiriyanto, Novan; Hafiz, Muhammad (Politeknik Negeri Lhokseumawe, 2025)
Solar energy is a sustainable and widely available resource with minimal environmental impact and low maintenance requirements. Ensuring the structural integrity of photovoltaic (PV) module supports is crucial for safe and efficient operation. This study utilizes FreeCAD, an open-source software with finite element analysis (FEA) capabilities, to evaluate the deformation and stress distribution in a solar-powered charging station structure. Two thickness variations (3 mm and 1.5 mm) of hollow carbon steel supports were analyzed under identical loading conditions. Results indicate that reducing the thickness from 3 mm to 1.5 mm increased deformation by 69.81% (from 0.53 mm to 0.9 mm) and stress by 96.93%, both remaining within acceptable structural tolerance limits. These findings validate FreeCAD as a cost-effective alternative to commercial FEA software, leveraging open-source libraries like Python, Calculix, and Open Cascade Technology (OCCT) to perform complex simulations without expensive licenses or high-end hardware.